Japan and Foreign Territory Strike: Debate, Deterrence, and Defense Strength - Corey Wallace (Master's Programs in International Relations, Faculty of Social and Political Science, Jenderal Achmad Yani University (UNJANI)., 2021)
The increased frequency of debate in Japan over foreign territory strike points to it being officially affirmed as a Japanese Self-Defense Force (SDF) mission in the near future. This article explores the foreign territory strike debate through the lens of the four key questions that have structured the post-war debate on all new overseas SDF operations: is it constitutional?; is it (militarily) plausible?; is it (strategically) wise?; and, is it (politically) acceptable? After discussing the contours of the Japanese post-war legal and policy debate on the use of force in foreign territory, the article describes contemporary doubts over the tactical effectiveness and strategic opportunity cost of configuring the SDF to conduct overseas strike operations—especially for missile defense purposes. Foreign territory strike would divert scarce fiscal resources and political attention from adaptations that enhance the US-Japan alliance’s posture resilience and enable it to sustainably generate force even after an initial attack, thereby augmenting regional deterrence. The article concludes by noting that political barriers could also still prevent the mission from being substantively and credibly implemented. Acrimonious domestic debate on foreign territory strike could also hamstring government attempts to attract public buy-in for future defense transformation in areas of greater priority and that add more to deterrence than the acquisition of modest strike capabilities.